Clinicopathological Study of Mucinous Carcinoma of Breast with Emphasis on Cytological Features: A Study at Tertiary Care Teaching Hospital of South India - Chikkannaiah, Panduranga; Thangngeo, Deinu; Guruprasad, Chanigaramaiah; Venkataramanappa, Srinivasamurthy (Journal of Laboratory Physicians, 2020)
Introduction Mucinous carcinoma (MC) is a rare form of breast cancer. It accounts for 1 to 7% of the cases and characterized by the presence of extracellular mucin (ECM). Depending on the amount of mucin, it is classified into pure mucinous carcinoma (> 90%, PMC) and mixed mucinous carcinoma (MMC; < 90%). In comparison to most common subtypes, MC is having better prognosis. There exist clinicopathological differences among PMC and MMC and also MC and IDC-NOS.Materials and Methods MCs diagnosed between January 2012 and December 2017 were included. Fine needle aspiration cytology smears were screened for cellularity, ECM, nuclear pleomorphism, signet ring cells (SRC), mucinophages, and myxovascular fragments (MVF). Histopathology slides were screened to confirm the diagnosis. Immunohistochemistry slides were graded as per the standard protocol. Statistical analyses were performed by SPSS software.Results In the present study, MC constituted 3.3%. The mean age of the patients was 50.9 years. ECM, mucinophages, and SRC were the key diagnostic cytological features. The PMC and MMC were clinicopathologically distinct with respect to gross findings and lymph node status. MMCs were highly proliferative. The mean duration of follow-up was 24.5 months. Complications were more common in MMC than PMC. Lymph node involvement is the key prognostic factor and it is independent of other prognostic factors like age, size, and hormonal receptor status.Conclusion PMC are rare subtype of breast cancer. The diagnostic cytological features are ECM, MVF, and SRC. MMC and PMC are clinicopathologically and genetically distinct.
Keywords: breast carcinoma; mucinous carcinoma; FNAC; extracellular mucin; mucinophages; signet ring cells; myxovascular fragments